Investigation of changes in the sensitivity of a fiber Bragg grating to temperature and strain using coatings from low-melting metal - Maiorova, E.A.; Varzhel, S.V.; Klishina, V.A.; Kozlova, A.I. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
We carried out the development and study of methods for changing the sensitivity of Fiber Bragg Gratings (FBG) to temperature and strain by applying various low-melting metals. Investigation of sensitive elements based on SMF-28 single-mode optical fibers with formed FBG and various metal coatings applied over the fiber have been made. The influence of FBG coating with low-melting metals on its sensitivity to temperature and deformation has been studied. Various fiber-optic sensitive elements have been developed, which are fibers with fiber Bragg gratings formed in them, while coatings of various thicknesses of tin or solder in the form of an alloy of tin and lead (Sn63Pb37) were deposited on the area with such diffraction structures. The presented experimental data are in good agreement with the calculated ones. The temperature sensitivity of the Bragg grating resonance with a solder or tin coatings is 4 times higher than the sensitivity of an uncoated grating. In turn, the analysis of the sensitivity to stretching allows us to conclude that, in comparison with the standard FBG, the sensitivity of the grating in the coating decreases and is about 0.017 pm/(µm/m) compared to 1.2 pm/(µm/m) (for the wavelength of the Bragg resonance 1530 nm) for a standard FBG without coating. The results obtained can be used to control and change the FBG sensitivity to temperature and/or deformation, depending on the conditions of the problem being solved in the field of creating fiber-optic measuring devices.